Traces of the Prophetic Biography in the Poetry of Khwaja Ghulam Hasan Multani Shaheed: An Analytical Study - Dr. Abdul Basit; Dr. Syed Mujahid Hussain (Seerat Studies, 2025)
In the Sufi tradition of the Indian subcontinent, an appealing and impactful mode of presenting the life of the Prophet ﷺ is prominently manifested through Mawlid poetry and na‘tiyah (devotional praise). In the teachings of Sufi saints, “remembrance of the Beloved” and “obedience to the Beloved” occupy a central place, where the “Beloved” refers to the august person of the Messenger of Allah ﷺ. For this reason, among Sufi poets, the depiction of the Prophetic biography ﷺ is not merely an expression of devotion and love, but also a means of spiritual training and adherence to the Prophetic model ﷺ. Hafiz Jamalullah Multani (d. 1250 AH) is among the distinguished Sufis of the subcontinent whose discourses (malfuzat) articulate the spiritual and ethical dimensions of the Prophetic biography ﷺ with profound influence and intellectual insight. His disciple, Khwaja Ghulam Hasan Multani Shaheed, rendered this Sufi understanding of the Prophetic life into poetic form in his renowned work Anwar-e-Jamaliyah. The seventeen Persian na‘ts included in the preface of this book are derived from the gatherings of Hafiz Jamalullah Multani’s malfuzat, presenting a luminous example of the Mawlid poetic tradition. In these na‘ts, along with portrayals of the beauty, perfection, and exalted status of the Messenger of Allah ﷺ, the poet’s fervent emotions, longing for vision, and yearning for union are vividly evident. In this way, Anwar-e-Jamaliyah becomes a beautiful synthesis of Sufi spirituality, poetic art, and Prophetic biography, offering the tradition of Mawlid al-Nabi ﷺ in the religious and literary context of the subcontinent with a renewed intellectual and aesthetic dimension. This article presents a research-based and analytical study of the traces of the Prophetic biography ﷺ in the poetry of Khwaja Ghulam Hasan Multani Shaheed, in order to better understand the trends, intellectual background, and literary impact of Sufi approaches to Prophetic biography.